Promoting Chinese urban residents' participation in source separation and recycling. (15th February 2022) - Gu, Binxian; Yao, Yanbin; Hang, Huimin; Wang, Yulin; Jia, Renfu; Liu, Lingxuan; Ling, Hui; Tang, Xinyi; Zhang, Haijie; Wu, Zhiwei; Wu, Yongxiang; Fujiwara, Takeshi; et al.
Highlights: Localized structural equation models are estimated for the 13 cities of Jiangsu. Residents' intentions to participate in source separation and recycling are quantified. Main influencing factors and their degrees of influence are identified across cities. Tailored and localized management strategies are proposed. Abstract: Source separation and recycling (SSR) for municipal solid waste is an important strategy for the transition to a circular economy and requires broader resident participation. How can residents' participation in SSR be promoted? Here, we consider 13 cities in Jiangsu as microcosms of China. We quantify residents' intentions to participate in SSR by distributing a validated questionnaire to 2, 963 urban residents, analyze the results through structural equation modeling, and propose localized policy recommendations. We find that residents have positive attitudes toward SSR, although 92.6% of residents in southern Jiangsu were more willing to participate than those in northern Jiangsu (84.6%). Additionally, the influencing factors and their degree of influence on resident SSR participation intentions exhibit disparities across cities. "Accessibility of SSR facilities" simultaneously affects the 13 studied cities and is a key factor. "Environmental knowledge" and "environmental attitudes" are important impact factors, with occurrence frequencies of 84.6% and 69.2%, respectively. However, laws and regulations have no significant effect on residents' SSR participation intentions. We recommend that the government create favorable external conditions related to facilities and services, promote extensive publicity and educational activities through various channels, and improve the effectiveness of SSR laws and regulations. Future SSR management strategies should be localized, flexible and comprehensive. This research could help decision makers in China and other countries design policy guides to promote SSR and help link current research areas to social development.